Sistema inteligente para la selección de brocas de perforación de pozos - Morooka, C. K.; Mendes, J. R. P.; Penha, M. A. V. R. da; Guilherme, I. R. (My University, 2003)
The present work begins with a review of the literature on bit selection methods for oil well drilling. A proposal for the structure and organization of a drilling database and a knowledge base, is described. Previous studies formed the principal elements in the process of selection of drills for proposed drilling. The procedure was implemented as a computer system for the selection of tricone bits. A drilling bit database for three different Brazilian sedimentary basins was obtained for several wells drilled, and knowledge was collected from drilling engineers from different fields both electronically and also by means of interviews. It can be concluded that the selection process showed good results based on tests, which were carried out.
Intelligent system for oil well drill bit selection
Keywords: Drill bit selection; Intelligent system; Knowledge base; Oil well drilling; Database systems; Sedimentary rocks; Intelligent systems; Knowledge based systems